Characterization of M-curcumin complexes (M= Cu, Co, Ag) in turmeric rhizome as sensitizer candidates in dye-sensitized solar cell (DSSC) - Jariah, Ainun; Hadisaputra, Saprizal; Purwoko, Agus Abhi (Acta Chimica Asiana, 2023)
This experimental research aims to characterize the complex compound M-curcumin (M=Cu, Co, Ag) based on turmeric (Curcuma longa Linn) rhizome as a candidate for photosensitizer in solar cells. The basic material used for manufacturing the M-curcumin complex compound in this study was curcumin from turmeric rhizome extract added to Cu2+, Co2+, and Ag+ metal ions. The results of the synthesis of the M-curcumin complex were characterized by FTIR and Uv-Vis spectrophotometers. The FTIR spectrophotometer test showed a curcumin compound in the viscous curcumin extract, characterized by an absorption wave number corresponding to the curcumin compound. In the M-curcumin complex, the bond between the metal and the ligand only appears in the Co-curcumin complex at the absorption number of 498.77 cm -1. The results of the UV-Vis spectrophotometer test showed that the maximum wavelength absorption in curcumin extract was 430 nm (abs = 0.688), Cu-Curcumin complex lmax 300 nm (abs = 2.573), Co-curcumin complex lmax 425 nm (abs = 1.067), and complex Ag-Curcumin lmax 430 nm (abs = 1.36). The UV-Vis and FTIR characterization showed that the Co-curcumin complex has good potential compared to the organic compounds (curcumin) and can be used as an alternative photosensitizer in solar cells